Self-assessment of future research skills teachers in research activities in the system of social partnership - V. B. Dankova (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. The relevance is justiﬁed by the rapid expansion of the educational space in the conditions of transformations of modern society and the labor market, which intensiﬁes the revision of the content of teacher education and the process of training young specialists. Both in the world and in Russia, there is a growing demand for students to develop independent experience in research and development in the process of studying at a university, in connection with which it becomes extremely important to comprehensively study the self-assessment of an individual’s research skills in professional self-determination and methods of self-realization in the social system. However, the problem is that research activities (REA) to develop self-assessment of students’ research skills are impossible without participants in partnership interaction in university training, in the context of the implementation of the “Three Missions of the University”.Goal. To identify and present a comprehensive self-assessment of groups of research skills of students – future teachers in the scientiﬁc research institute.Materials and methods. The methodological basis for determining the characteristics of self-assessment of groups of research skills in scientiﬁc research works was compiled to achieve the set goal using the following methods: general scientiﬁc method of analyzing scientiﬁc and pedagogical literature; survey method; method of mathematical and statistical data processing using a licensed version of the spreadsheet editor Microsoft Excel 2010.Results and discussion. The study for the ﬁrst time proposed a self-assessment of the research skills of groups of students – future teachers at the Research Institute, which makes it possible to describe with the participants in partnership possible options for personal development in accordance with the ideals of society for a given period of time in the context of the implementation of the “Three Missions of the University”.Conclusion. Based on the results of the study, we can conclude that the practical signiﬁcance lies in the fact that the proposed empirical material in students’ research and development activities is in demand in teacher education. Of particular importance for the administration and teachers of universities is the possibility of synchronizing demand and supply in the labor market and determining the management strategy in the context of the implementation of the “Three Missions of the University”.